Assessing Perceived Nursing Competence of Final Year Students of Selected Nursing Colleges - Peter, Lissa; Marath, Usha; Thomas, Aalbina; Santhosh, Aiswarya; Joy, Aleena; Shaju, Aneena; Devis, Annmariya (Innovations in Pedagogy and Technology, 2026)
Lack of clinical competence remains a significant concern in impacting the quality of nursing care. In today’s complex healthcare environment, the delivery of high-quality nursing care increasingly depends on the competence of nursing professionals. Recognizing this, the present study aimed to assess the perceived nursing competence of final-year undergraduate nursing students from selected nursing colleges, with the goal of identifying potential gaps and informing educational strategies to better prepare graduates for professional practice. A non-experimental descriptive research design was employed. A total of 200 final-year undergraduate nursing students were selected through convenience sampling. Data were collected using a structured rating scale to assess students’ perceived nursing competence. In this study, 36.5% of nursing students perceived their overall competence as excellent, 59% as good, 4% as average, and 0.5% as poor. No students rated their competence as very poor. In specific areas, 60.5% perceived excellent competence in basic nursing skills, while 42% reported average competence in advanced skills. Additionally, 59.5% perceived good competence in core nursing competencies, and 59% rated their professional nursing behaviors as excellent. Competence is essential for safe and effective nursing practice. Strengthening educational preparation is crucial to ensure students gain the confidence and skills needed for clinical practice.